1999
DOI: 10.1094/phyto.1999.89.12.1176
|View full text |Cite
|
Sign up to set email alerts
|

Helper Component Mutations in Nonconserved Residues Associated with Aphid Transmission Efficiency of a Pepper Isolate of Potato Virus Y

Abstract: The aphid transmission properties of a pepper isolate of potato virus Y belonging to the pathotype 1-2 (PVY 1-2) have been characterized. PVY 1-2 was not transmitted in plant-to-plant experiments, although purified virus particles were efficiently transmitted when supplemented with heterologous helper component (HC) of the transmissible isolate PVY 0 AT through membrane acquisition assays, indicating that its coat protein was functional in transmission. Additionally, virions of PVY 1-2 were able to bind to dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The latter group lacks a helper component protein acting as a bridge during the transmission process, and therefore variability in the ability to transmit is restricted to changes in the coat protein (CP) of the virus (Perry, 2001). A variation in the transmissibility of potyviruses can thus result from mutations in either the CP or the helper component protein (HC-PRO) (Atreya et al, 1991;Granier et al, 1993;Blanc et al, 1998;Llave et al, 1999;López-Moya et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The latter group lacks a helper component protein acting as a bridge during the transmission process, and therefore variability in the ability to transmit is restricted to changes in the coat protein (CP) of the virus (Perry, 2001). A variation in the transmissibility of potyviruses can thus result from mutations in either the CP or the helper component protein (HC-PRO) (Atreya et al, 1991;Granier et al, 1993;Blanc et al, 1998;Llave et al, 1999;López-Moya et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, it was also shown that HCPro plays a key role in the semi-persistent dispersion of Wheat streak mosaic virus (WSMV), a member of the Tritimovirus genus transmitted by eriophyid mites (Stenger et al, 2005b). Moreover, despite the low overall sequence similarity between the tritimovirus and potyvirus HCPros, mutations in conserved cysteine residues affected the transmission process in viruses belonging to these two genera (Atreya and Pirone, 1993;Llave et al, 1999;Young et al, 2007). As a detailed characterization of the role of HCPro in transmission mediated by vectors other than aphids awaits to be addressed, it is not currently clear whether this function has been acquired independently in different Potyviridae genera (convergent evolution), or has been derived from a common ancestral virus that was transmitted by an ancestral arthropod (adaptation).…”
Section: Transmission-a Historical Overview Of Hcpro Discoverymentioning
confidence: 99%
“…A collection of PVY isolates from different geographical origins were used in this work: an aphid-transmissible Scottish isolate from potato of the PVY O common strain group (PVY O SCRI-O) described by Barker et al [20]; a non-aphid-transmissible isolate, also of the PVY O -strain group, obtained from pepper plants in Southern Spain (PVY 1-2, isolate P-22-88) [21,22]; and several isolates that were sampled from field-grown crops in the month of August, at the start of the main potato growing season, in two separate locations in Tunisia: one site by the coast (Monastir, Lat. 35.7345/Long.…”
Section: Virus Isolatesmentioning
confidence: 99%
“…Amplification by PCR of the HCPro cistrons from cDNAs was performed using highfidelity Phusion Tm DNA polymerase (Invitrogen). Oligos specific for the Scottish and Spanish accessions were designed (Table 1) using their already known nucleotide HCPro sequences [20], GenBank accession number AJ585196.1 of the whole viral sequence and [21], GenBank accession number AF166115, respectively. For the Tunisian isolates, degenerate oligos were used, which once the fragments had been cloned, turned out to have the sequences shown in Table 1.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation